Evolusi Pendidik di Era Moderenisasi dengan Mengembangkan Profesionalisme Profil Tenaga Pendidik - Munawir, Munawir; Khoiriyah, Qurrotun Nufus Khoiriyah; Ifkaruddin, Muhammad Naufal (Lembaga Intelektual Muda (LIM) Maluku, 2025)
Education in Indonesia has undergone major changes over time, influenced by social, political, and cultural factors. The role of teachers has also evolved, not only as teachers, but also as innovators and motivators. The demands for professionalism are increasing, including mastery of technology, increasing pedagogical competence, and strengthening character and professional ethics. This study aims to analyze the evolution of the role of educators in the era of modernization that has an impact on increasing the professionalism of educators, as well as strategies that can be applied in its development. The research method used is the Qualitative Research Method, with an approach used to gain a deeper understanding of social phenomena by analyzing non-numerical data. The results of the study show that the development of professionalism of educators can be carried out through ongoing training, the application of technology in learning, and collaboration in professional communities. With continuously improving professionalism, educators are able to create a learning ecosystem that is more adaptive, innovative, and in accordance with the needs of 21st century education